Investigating the price volatility transmission mechanisms of selected fresh vegetable chains in Greece. Issue 5 (16th April 2020) - Rezitis, Anthony N.; Pachis, Dimitrios N.
Abstract : Purpose: This paper attempts to model the transmission of volatility between producer and consumer prices in the fresh potato, tomato, and cucumber markets in Greece. Design/methodology/approach: The transmission mechanism of the price volatility is modeled using the most popular multivariate GARCH models while taking into consideration possible asymmetries in the transmission process. The models utilized are the DVECH and the BEKK models from the VECH family, as well as the CCC model and the DCC model from the family of conditional correlation models. The possible asymmetric effects are evaluated using asymmetric GARCH models, as well as estimating volatility impulse responses for independent shocks. Findings: The results reveal that, in the tomato and cucumber markets, which are regulated by the Common Market Organization of fruits and vegetables, producers are less vulnerable to volatility shocks transmitted from consumers. In contrast, in the non-regulated potato market, producers are affected by spillover effects from consumers. Research limitations/implications: This study is limited to a few commodities (i.e. potatoes, tomatoes, and cucumbers); however, it could be extended to additional commodities. Practical implications: The results of this study show that, if producers are organized on a cooperative basis within the regulative framework of the CAP, like the tomato and cucumber producers, their place in the food supply chain is strengthened, although the CAP targets more market-oriented agricultural markets that are more exposed to world prices. Originality/value: The present study attempts to understand the transmission of volatility between producer and consumer prices in the fresh potato, tomato, and cucumber markets in Greece, which is not apparent from previous studies. Furthermore, the volatility clusters that are identified in the present study are associated with certain CAP reforms.